Broken country (reese's book club) ebook - Hall, Clare Leslie (2025)
A REESE'S BOOK CLUB PICK " Broken Country by Clare Leslie Hall is an unforgettable story of love, loss, and the choices that shape our lives...but it's also a masterfully crafted mystery that will keep you guessing until the very last page. Seriously, that ending?! I did not see it coming." —Reese Witherspoon "Stirring and mysterious...fires directly at the human heart and hits the mark." —Delia Owens, New York Times bestselling author of Where the Crawdads Sing A love triangle unearths dangerous, deadly secrets from the past in this thrilling tale perfect for fans of The Paper Palace and Where the Crawdads Sing . "The farmer is dead. He is dead, and all anyone wants to know is who killed him." Beth and her gentle, kind husband Frank are happily married, but their relationship relies on the past staying buried. But when Beth's brother-in-law shoots a dog going after their sheep, Beth doesn't realize that the gunshot will alter the course of their lives. For the dog belonged to none other than Gabriel Wolfe, the man Beth loved as a teenager—the man who broke her heart years ago. Gabriel has returned to the village with his young son Leo, a boy who reminds Beth very much of her own son, who died in a tragic accident. As Beth is pulled back into Gabriel's life, tensions around the village rise and dangerous secrets and jealousies from the past resurface, this time with deadly consequences. Beth is forced to make a choice between the woman she once was, and the woman she has become. A sweeping love story with the pace and twists of a thriller, Broken Country is a novel of simmering passion, impossible choices, and explosive consequences that toggles between the past and present to explore the far-reaching legacy of first love.